Control of maternal Zika virus infection during pregnancy is associated with lower antibody titers in a macaque model - Krabbe, Nicholas P.; Razo, Elaina; Abraham, Hunter J.; Spanton, Rachel V.; Shi, Yujia; Bhattacharya, Saswati; Bohm, Ellie K.; Pritchard, Julia C.; Weiler, Andrea M.; Mitzey, Ann M.; Eickhoff, Jens C.; Sullivan, Eric; et al. (Frontiers in Immunology, 2023)
Zika virus (ZIKV) infection during pregnancy results in a spectrum of birth defects and neurodevelopmental deficits in prenatally exposed infants, with no clear understanding of why some pregnancies are more severely affected. Differential control of maternal ZIKV infection may explain the spectrum of adverse outcomes. Here, we investigated whether the magnitude and breadth of the maternal ZIKV-specific antibody response is associated with better virologic control using a rhesus macaque model of prenatal ZIKV infection. We inoculated 18 dams with an Asian-lineage ZIKV isolate (PRVABC59) at 30-45 gestational days. Plasma vRNA and infectious virus kinetics were determined over the course of pregnancy, as well as vRNA burden in the MFI at delivery. Binding and neutralizing antibody assays were performed to determine the magnitude of the ZIKV-specific IgM and IgG antibody responses throughout pregnancy, along with peptide microarray assays to define the breadth of linear ZIKV epitopes recognized. Dams with better virologic control (n= 9) cleared detectable infectious virus and vRNA from the plasma by 7 days post-infection (DPI) and had a lower vRNA burden in the maternal-fetal interface (MFI) at delivery. In comparison, dams with worse virologic control (n= 9) still cleared detectable infectious virus from the plasma by 7 DPI but had vRNA that persisted longer, and had higher vRNA burden in the MFI at delivery. The magnitudes of the ZIKV-specific antibody responses were significantly lower in the dams with better virologic control, suggesting that higher antibody titers are not associated with better control of ZIKV infection. Additionally, the breadth of the ZIKV linear epitopes recognized did not differ between the dams with better and worse control of ZIKV infection. Thus, the magnitude and breadth of the maternal antibody responses do not seem to impact maternal virologic control. This may be because control of maternal infection is determined in the first 7 DPI, when detectable infectious virus is present and before robust antibody responses are generated. However, the presence of higher ZIKV-specific antibody titers in dams with worse virologic control suggests that these could be used as a biomarker of poor maternal control of infection and should be explored further.